PENGARUH UKURAN PEMERINTAH DAERAH, UKURAN LEGISLATIF DAN OPINI AUDIT BPK TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Bagus Ario Wibowo, - (2019)
This research was conducted to examine the effect of Local Government Size, Legislative Size and BPK Audit Opinion. This research using local government (kabuaten/kota) in province central java in the sample. Sampling technique uses purposive sampling method. Sampling of 105 provinces in indonesia in 2015 up to 2017. The secondary data of this research is in the form of BPK Examination Report the results of the examination on local government financial report. The testing of hypotheses in this research using analysis of multiple linear regression with the program spss 23 and the level significance 5 percent. The results of the study partially show that the size of the Regional Government has a significant effect on the Regional Government Financial Performance with a significance level of 0.006 smaller than the specified level of a = 0.05, Legislative Size has a significant effect on Local Government Financial Performance with a significance level of 0,000 smaller of the significance level determined a = 0.05 and BPK Audit Opinion did not significantly influence the Regional Government Financial Performance with a significance level of 0.406 greater than the significance level specified a = 0.05.